Clinical Decision Making of Electrophysiological Agents by Physical Therapists - Noor-ul-Huda, Mehwish Khalid, Iqra Ishriaq, Ammara Abbas, Zainab Hassan, Syed Ali Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Therapeutic modalities play a major role in rehabilitation and assist other therapeutic treatments, such as physical exercise and manual therapy. Aim: To assess the factors that affect the clinical decision making of electrophysiological agents by physical therapists. Study design: Descriptive cross-sectional survey. Methodology: Sample was taken through non- probability sampling technique. Sample size was calculated through Census method. Data was collected through online survey and questionnaires that were randomly distributed to all clinical physical therapists. Data was evaluated by using SPSS vr 24. Quantitative variables are represented in the form of frequencies %age. Results: 31(54%) of PTs reported Research evidence as a strong factor, 30(52%) reported availability of equipment and 40(70%) of PTs reported past clinical experience as a strong factor that influence the decision of usage of electrophysiological agents. The most frequently available agents were ultrasound (96%), hot pack (98%), cold pack (96%) and TENS (98%). Practical Implication: This study has determined the influence of various factors that affect the clinical decision-making abilities of clinical physical therapists working in Pakistan. Conclusion: It was concluded that making a decision while using EPAs was a complex phenomenon. All the factors must be considered when using EPA as treatment modality. Furthermore, there must be a regular check-up regarding the availability and up-dated version of EPAs by health policy makers in all clinical settings. Keywords: Electrophysiological Agents, Therapeutic Modalities and Rehabilitation.